The need for accounting training packages for small-scale firms in rural Mauritius - Betchoo, Nirmal Kumar (Advances in Social Sciences Research Journal, 2015)
This paper basically examines the need for accounting education and training for small-scale businesses in Mauritius and the need to use accounting software packages in such organisations. For the purposes of the study, the researcher selected two locations namely Pamplemousses and Flacq as areas where the research could be undertaken. Around thirty small businesses were targeted with a turnover varies between Rs 125 000 to Rs 1 million. The research states that there is a positive perspective of using accounting software packages in Mauritius regarding small firms. The companies selected for the purpose of the research were in favour of adapted accounting packages that they could effectively use for the day-to-day activities while ensuring that they adopt the regulatory business practices. Although the research is valid within the parameters defined; thirty companies on average, two rural districts in Mauritius, it cannot be co seven coastal ones. The practical implication of the research is that small-scale businesses in rural areas of Mauritius require tailor-made accounting packages to perform better. The use of accounting packages might encourage small-scale businesses in rural Mauritius to be future-oriented and ready to face long-term survival. This research is undertaken at a time when Mauritius calls for good financial governance and performance from small businesses when accounting packages can effectively boost efficiency and effectiveness.